Trajectory and Determinant of Functional Independence among Patient with Traumatic and Non-Traumatic Spinal Cord Injury - Yudha Mathan Sakti; Astri Ferdiana; Dananjaya Putramega; Zikrina A. Lanodiyu; Galih Prasetya Sakadewa; Rahadyan Magetsari (International Journal of Public Health Science (IJPHS), 2018)
The level of functional independence was directly proportional to life satisfaction and quality of life in patients with spinal cord injury. By knowing the determinants that predict changes in functional independence, medical treatment and rehabilitation can be better planned to improve the patient’s quality of life. We conducted a prospective cohort study on 49 patients with spinal cord injury at Dr. Sardjito general hospital Yogyakarta from April to June 2016. The data were taken before patient underwent surgery, before discharged from the hospital, and 3 months after underwent surgery. We found that most common spinal cord injury was at the level of lumbar vertebra with 28 patients (58%). There was a positive trajectory of the patients with spinal cord injury with ASIA grade B-E classification. However, patients with spinal cord injury with ASIA classification grade A have a neutral trajectory.We conclude there was a positive trajectory between functional independence and traumatic or non-traumatic spinal cord injury except in patients with ASIA grade A classification spinal cord injury. The determinants that affected the trajectory of patients with spinal cord injury were the level of the injured vertebra and severity of the neurological deficit.